Food insecure student clients of a university‐based food bank have compromised health, dietary intake and academic quality. Issue 1 (2nd August 2016) - Farahbakhsh, Jasmine; Hanbazaza, Mahitab; Ball, Geoff D.C.; Farmer, Anna P.; Maximova, Katerina; Willows, Noreen D.
Abstract : Aim: University and college students in wealthy countries may be vulnerable to financial food insecurity. If food insecure students have suboptimal health, their ability to learn and excel in their education could be compromised. This Canadian study examined the relationship of food security status to diet and self‐perceived health and academic quality among students receiving emergency food hampers from the Campus Food Bank at University of Alberta. Methods: A convenience sample of 58 students completed a survey. Results: Of participating students, 10.3% were food secure, 44.8% were moderately food insecure and 44.8% were severely food insecure. Overall, 32.8% rated their general health as fair/poor, 27.6% rated their mental health as fair/poor and 60.3% indicated at least one adverse academic outcome of not having enough money for food. Compared to other participating students, students with severe food insecurity had a greater likelihood of fair/poor general health (odds ratios (OR) 4.03, 95% confidence intervals (CI) 1.10–14.78); fair/poor mental health (OR 4.96, 95% CI 1.28–19.19); being unable to concentrate in class or during an exam (73.1% vs 40.6%, χ 2 = 6.12, P = 0.013); relying on food hampers (34.6% vs 9.7%, χ 2 = 5.57, P = 0.018); and, consuming fewer daily fruits, vegetables and legumes (2.12 vs 2.97 cup equivalents, P = 0.009). Conclusions: Food insecurity compromises students' health, diet and academic quality. Campus food banks are not the solution to student hunger. Governmental and university‐based programmes and policies are needed to improve the food security situation of university students.